Pengaruh EVA, Firm Size, DPR, Dan PBV Terhadap Harga Saham Perusahaan Manufaktur - Linda Angelina, Susanto Salim (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is to analyze the effect of EVA, firm size, DPR, and PBV  on share prices of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The data used in this study were 141 companies using purposive sampling technique. The software used in processing data is Eviews 10.0. F test result show EVA, firm size, DPR, and PBV together have a significant effect on stock prices. T test results show that EVA has a negative and significant effect on stock prices. Firms size has a negative and not significant effect on stock prices, while the DPR and PBV have a positive and not significant effect on stock prices.